Be Careful What You Wish For: Issues in the Statutory Regulation of Counsellors - Handelsman, Mitchell M.; Uhlemann, Max R. (Canadian Journal of Counselling and Psychotherapy, 2009)
The purpose of this article is to examine important elements of the decision of whether and how counselling should be\ regulated by statute. First, the current status of certification, registration, and licensure of counselling in Canada is presented. This is followed by a presentation of nature and components of regulatory schemes in North America along with important issues associated with each one, focusing on the pitfalls and unintended negative consequences inherent in regulation. Finally, it is recommended that provincial counselling associations should answer four fundamental questions when they consider applyng for statutory regulation.